MANUSIA DAN DUNIA: KONSEP KRISTOLOGI DENGAN PERSPEKTIF REFORMED - Suryowati Wang (Sekolah Tinggi Teologi Excelsius, 2020)
Humans are special creatures of God with their true nature as guardians of the earth. The purpose of writing to find answers about human meaning, the meaning of the world, and how human relationships and their world? The study uses qualitative methods with a philology approach. The results of the study are: (1) man is not just a creation, he is also a person. Being a person means being able to make decisions, set goals, and move towards those goals. Humans are not robots whose actions are determined by forces outside themselves. To be one person means to be a